2013
DOI: 10.1287/mnsc.1120.1699
|View full text |Cite
|
Sign up to set email alerts
|

License to Cheat: Voluntary Regulation and Ethical Behavior

Abstract: While monitoring and regulation can be used to combat socially costly unethical conduct, their intended targets are often able to avoid regulation or hide their behavior. This surrenders at least part of the effectiveness of regulatory policies to firms' and individuals' decisions to voluntarily submit to regulation. We study individuals' decisions to avoid monitoring or regulation and thus enhance their ability to engage in unethical conduct. We conduct a laboratory experiment in which participants engage in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 71 publications
4
52
0
Order By: Relevance
“…10This gender difference in performance is consistent with previous findings (e.g., Brown and Josephs 1999;Gino, Krupka and Weber 2013) and is particularly important for understanding the main results of the paper (Result 4). Although it is found that men and women choose the same allocation choices (Result 2), we will see that women's behavior is sensitive to the context and women are inclined toward choosing a convenient allocation.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…10This gender difference in performance is consistent with previous findings (e.g., Brown and Josephs 1999;Gino, Krupka and Weber 2013) and is particularly important for understanding the main results of the paper (Result 4). Although it is found that men and women choose the same allocation choices (Result 2), we will see that women's behavior is sensitive to the context and women are inclined toward choosing a convenient allocation.…”
supporting
confidence: 87%
“…Although the regression analysis suggests that there is no effect of the relative performance on the probability of being self-serving, recent evidence suggest that disadvantage individuals might have a tendency to overcome their disadvantage by cheating (e.g., Schwieren and Weichselbaumer 2010;Gino, Krupka and Weber 2013).…”
mentioning
confidence: 93%
“…This would have made the moral component, M more significant for the investment decision. Because investors in our study are not subject to scrutiny from others, there is no image concern (see Ariely et al 2009; see also Gino et al 2013), i.e., the moral benefit of responsible investing decreases. Thus, the moral benefit rather relates to the investor's self-identity, i.e., the extent to which the investor is able to act in a manner that is consistent with his or her beliefs and values (see Tirole 2006, Meier 2007).…”
Section: Resultsmentioning
confidence: 99%
“…While we cannot detect lying at the individual level, the aggregate distribution of reported performance values allows us to detect, statistically, the degree of misreporting (cf. Houser, et al, 2012;Fischbacher and Föllmi--Heusi, 2013;Gino, et al, 2013). The task is performed only once in Stage 1 and afterwards all subjects are informed about the average reported performance across all subjects, the total size of the prize, and their own payoff for Stage 1.…”
Section: First Stagementioning
confidence: 99%